A review of reactive transport modeling in wellbore integrity problems - Ajayi, Temitope; Gupta, Ipsita (Journal of petroleum science & engineering, 2019)
Long term assurance of the integrity of wellbores is a key objective in well designs. Over long periods of time, subsurface reactions are inevitable and could compromise the integrity of wells. Reactive transport has come to be known to play an important role in the understanding of subsurface processes and assessing wellbore integrity issues. A considerable body of work exists in the literature on this subject matter necessitating an up to date review. In this paper we discuss the numerical formulations, assumptions, solution methods and limitations that provide a framework for these studies. Expected chemical reactions such as corrosion, cement bonding and transport phenomena (advection, diffusion, dispersion) in wellbore integrity issues are elucidated. Important studies which show the direction of research in wellbore integrity reactive transport modeling (RTM) are discussed. Future research directions and current gaps in the field that have been identified are the need for multiscale modeling, rigorous modeling of heterogeneities and incorporation of multiple physics. It is our hope that this review would provide the interested engineer with the current state of the science for reactive transport in wellbore integrity and provide a solid foundation for interested researchers to further expand the current knowledge in this field. •A comprehensive review of the applications of reactive transport modelling to wellbore integrity studies.•A discussion on relevant cement chemistry to wellbore integrity problems.•A summary of experimental and numerical work done in reactive transport applications for wellbore integrity issues.•Current gaps and possible research directions (scale issues, complex heterogeneities, multi-physics and subsurface interactions).